IDENTIFICATION OF THERMAL MATURITY, SOURCE AND DEPOSITIONAL ENVIRONMENT FROM CORE SAMPLE OBTAINED FROM UNDERWATER GEOCHEMISTRY SURVEY IN KABAENA SUB-BASIN, BONE BASIN, SOUTHERN PART OF SULAWESI - SYABAN, FARHAN TAUFIK; Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2019)
Bone Gulf in South Sulawesi is an area with the possibility of potential hydrocarbon deposits. This research was conducted to examine the characteristics of Hydrocarbons gotten from Core Extractionfrom underwater geochemistry survey in the area of study by geochemical analysis methods and compared with known geological data. Geochemical analysis was carried out on 27 seabed-core samples taken from the area around the Kabaena sub-basin to determine the maturity level and depositional environment and the source of organic material from the Hydrocarbon producing Source Rock. Determination of the maturity level and depositional environment is based on CPI and OEP value, as well as N-Alkane and Isoprenoids which obtained from Gas Chromatography (GC). Geochemical analysis for the maturity level of all the samples showed the maturity level of immature to mature. Geochemical analysis for depositional environments on all samples showed a tendency to be deposited in the transitional and the sources of organic material is Mixed Kerogen.Keywords:        Bone Gulf, Hydrocarbon, CPI and OEP, N-Alkane, Geochemistry Analysis, Source RockABSTRACTBone Gulf in South Sulawesi is an area with the possibility of potential hydrocarbon deposits. This research was conducted to examine the characteristics of Hydrocarbons gotten from Core Extractionfrom underwater geochemistry survey in the area of study by geochemical analysis methods and compared with known geological data. Geochemical analysis was carried out on 27 seabed-core samples taken from the area around the Kabaena sub-basin to determine the maturity level and depositional environment and the source of organic material from the Hydrocarbon producing Source Rock. Determination of the maturity level and depositional environment is based on CPI and OEP value, as well as N-Alkane and Isoprenoids which obtained from Gas Chromatography (GC). Geochemical analysis for the maturity level of all the samples showed the maturity level of immature to mature. Geochemical analysis for depositional environments on all samples showed a tendency to be deposited in the transitional and the sources of organic material is Mixed Kerogen.